Reaching deaf and hard-of-hearing people in audiovisual research - Motiejūnienė Jurgita (Specijalna Edukacija i Rehabilitacija)
Introduction. In many scientific domains, researchers encounter difficulties in recruiting subjects, respondents, or participants for interviews, surveys, or experiments, particularly when targeting hard-to-reach populations. Selecting appropriate recruitment methods is crucial for ensuring a representative sample, which enhances the validity and reliability of the research findings. Researchers have to consider ways of finding and inviting participants, communicating with them, motivating them to contribute to research, ensuring their anonymity (if necessary) and data security, navigating ethical concerns, considering compensation for participation, and much more. In the audiovisual domain, recruiting deaf and hard-of-hearing participants poses additional challenges due to communication barriers. Difficulties in recruiting such participants could potentially result in the underrepresentation of deaf and hard-of-hearing individuals in research. Objectives. This paper, through a systematic review of existing studies, aims to investigate diverse methods and challenges associated with recruiting deaf and hard-of-hearing participants in audiovisual research. Methods. A systematic review was performed following the PRISMA framework to gather information from reliable open access sources (n = 49) over the ten-year period from 2013 to 2023. Results. The analysis offers insights into the authorship, geographical distribution, participant demographics, and methods used to recruit deaf and hard-of-hearing participants. Conclusion. The two most effective recruitment methods for deaf and hard-of-hearing participants include collaboration with the deaf and hard-of-hearing associations and inviting participants through social media. Implementing a well-planned strategy is essential to ensure successful recruitment of participants.